2012
DOI: 10.1111/jfpp.12045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfites and Sorbates on the Preservation and Color of Pickled Blanched Garlic under Different Storage Conditions

Abstract: The influence of sulfites and sorbates on the microbial stability and color of pickled blanched garlic stored under different conditions was studied. Two storage temperatures (ambient, 20–24C; refrigeration, 6–9C) and two types of packaging (glass bottle, plastic pouch consisting of polyester/polyethylene/saran) were considered. Both sulfites and sorbates gave satisfactory results as antimicrobial agents, even at room temperature. Sulfite was also effective as an anti‐browning agent, but sorbate produced the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, soaking in sodium bisulphite solution produced garlic powder lighter than without soaking. Similar result are found by Casado et al, [6], who stated that L* value of pickle blanched garlic soaked in sodium bisulphite solution reach significantly higher values compared other treatment without soaking.…”
Section: Coloursupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, soaking in sodium bisulphite solution produced garlic powder lighter than without soaking. Similar result are found by Casado et al, [6], who stated that L* value of pickle blanched garlic soaked in sodium bisulphite solution reach significantly higher values compared other treatment without soaking.…”
Section: Coloursupporting
confidence: 89%
“…The use of additives IOP Publishing doi:10.1088/1755-1315/1024/1/012015 2 such as sodium bisulphite is a practice widely used by the industry to prevent browning reactions. It is most effective than other additives in preventing the green discoloration [6]. Some research result reported that sodium bisulphite can prevent discoloration of pumpkin powder [7] [8], banana [9], apple [9], potatoes [10], green coconut water [11], shallot [12] [13] [14], and garlic [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2009 found that pears treated with MeJA after harvest showed delayed rotting and did not adversely affect quality parameters such as titratable acidity (TA), firmness and soluble solids content (SSC). Researchers suggested that MeJA treatment resulted in higher level of TA compared with untreated fruit and had positive effects on fruit quality (Wang & Zheng 2005;Casado et al 2014;Akan et al 2019). In the current study, it was found that the fruit treated with 0.5 mM MeJA have a positive influence in terms of SSC.…”
Section: Discussionmentioning
confidence: 99%